2020
DOI: 10.1101/2020.12.15.422970
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved prime editors enable pathogenic allele correction and cancer modelling in adult mice

Abstract: Prime editors (PEs) mediate genome modification without utilizing double-stranded DNA breaks or exogenous donor DNA as a template. PEs facilitate nucleotide substitutions or local insertions or deletions within the genome based on the template sequence encoded within the prime editing guide RNA (pegRNA). However, the efficacy of prime editing in adult mice has not been established. Here we report an NLS-optimized SpCas9-based prime editor that improves genome editing efficiency in both fluorescent reporter cel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 53 publications
(109 reference statements)
1
29
0
Order By: Relevance
“…In our study, systemic injection of a single dose of AdV5 encoding the prime editing components into neonates resulted in an average of 58% editing at the Dnmt1 and 8% editing at the Pah enu2 locus. These rates are substantially higher than in recently reported prime editing studies in somatic tissues (20,45), and led to the restoration of physiological blood-L-Phe levels in Pah enu2 mice. Importantly, correction rates of approximately 10% in hepatocytes should also be sufficient to treat a variety of other genetic liver diseases, including tyrosinemia and urea cycle disorders (46)(47)(48).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In our study, systemic injection of a single dose of AdV5 encoding the prime editing components into neonates resulted in an average of 58% editing at the Dnmt1 and 8% editing at the Pah enu2 locus. These rates are substantially higher than in recently reported prime editing studies in somatic tissues (20,45), and led to the restoration of physiological blood-L-Phe levels in Pah enu2 mice. Importantly, correction rates of approximately 10% in hepatocytes should also be sufficient to treat a variety of other genetic liver diseases, including tyrosinemia and urea cycle disorders (46)(47)(48).…”
Section: Discussionmentioning
confidence: 59%
“…Since PEs directly write new genetic information, they are extremely versatile, and allow the installation of all possible nucleotide conversions as well as short deletions and insertions up to 80 bp (1). To improve editing efficiency of PEs, mutations that enhance the activity of the RT have been introduced (PE2) and a second sgRNA can be designed to nick the non-edited DNA strand either in parallel (PE3) or after installing the edit (PE3b), facilitating DNA repair of the edited DNA strand (1,19,20). While prime editing has already been demonstrated in vitro in cultured cells (1,(21)(22)(23) and in vivo in mice and Drosophila (19,20,24,25), treatment of animal models for human diseases via prime editing has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reporter Multi-Cas Variant 1 (TLR-MCV1) HEK293T reporter line for testing an 18-bp insertion (Supplementary Fig. 2a) 16,17 . Consistent with our results in mCherry reporter cells, RT362, RT418 and RT474 showed decreased on-target editing efficiencies (0.1%, 0.1%, and 3.4%, respectively).…”
mentioning
confidence: 99%
“…Finally, we tested the efficiency of precise deletion of PE2 variants using a second TLR reporter for testing a 47-bp insertion (Supplementary Fig. 2b) 16 . We found that RT474 and RT497 exhibited editing efficiencies that were similar to PE2 (3.2%, 4.4%, and 3.5%, respectively), while the editing efficiencies of RT362 and RT418 were decreased (0.1% and 0.2%) (Fig.…”
mentioning
confidence: 99%